A Case of Secondary Hyperparathyroidism with Metastatic Pulmonary Calcification: Discussing Treatment Options - Mütiş Alan, Aydan; Şentürk, Esra Fırat; Toker Dinçer, Zeynep; Dinçer, Mevlüt Tamer; Murt, Ahmet; Melikoğlu, Melike; Seyahi, Emire; Seyahi, Nurhan; Trabulus, Sinan (Cerrahpaşa Medical Journal, 2024)
Cite this article as: Mütiş Alan A, Şentürk EF, Dinçer ZT, et al. A case of secondary hyperparathyroidism with metastatic pulmonary calcification: discussing treatment options. Cerrahpaşa Med J. 2024;48(3):298-301.